Supporting the Quality Culture of Education through the Design of an Information Technology System for Accurate Management Services at Pondok An-Nahdloh Selangor - Aini, Desti Nur; Winarno, Agung; Rahman, Amalia Arifah (Westscience Press, 2024)
This research aims to design a management information system application based on the needs of internal administrative services, as well as testing the level of effectiveness of its application on service quality to support a culture of quality education, as well as assessing the constraints and challenges in the process of implementing the system based on aspects of human resources, facilities, and policy support. This research adopts a Research and Development (R&D) approach, with IPPPE stages (Identification of needs, Design, Testing, Implementation, and Evaluation). Data collection is in the form of questionnaire sheets for expert validators and users. The results showed that (1) the design of the management information system features a registration module, student and teacher data management module, grade management module, and financial management module. (2) The information system application developed has a high level of feasibility, as well as a level of effectiveness in supporting the accuracy and speed of service to internal management parties and supporting the culture of quality education. (3) There are several obstacles and challenges in the process of implementing management information systems, namely technical constraints and challenges, and user adaptation which includes the limited ability of application managers, limited infrastructure, and the need for future system development to integrate with the learning field.